Paciente de 16 años de edad embarazada con lesión de sitios contiguos del encéfalo. - Muñoz Pacheco, Héctor Joel (2021)
The alterations in the central nervous system produced by a lesion in the brain, the period of adolescence and the state of pregnancy, are three physical and metabolic changes that demand energy needs. Since, by presenting biochemical, physical, psychological and metabolic alterations, and not meeting these needs through a good diet plan given by a correct nutritional evaluation; the health status of the patient in question would run a greater risk than the one she already presents due to her alterations.